THE EFFECTIVE LEARNING ENGLISH TO IMPROVE STUDENT ABILITY IN WRITING - Nurhayati Nurhayati (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2011)
English is the first foreign in formally taught in school. English is the global language that is used by more than half the world population. Ongoing development in Indonesia is inseparable from science and technology absorption. This ability is certainly related to the improvement of human resources, including mastery of English. English has four skills, or complexes of skill; listening, speaking, reading, and writing. If student would like to write well and correctly in English, they have to master several items. Example: Grammar, Sentences, Subject verb agreement, Run-ons, fragment and the others that related to the writing skill.Keyword: teaching, writing skill and teaching technique.